Thoracic Coupled Motions of Korean Men in Good Health in Their 20s - Moon, Ok-Kon (The Society of Physical Therapy Science, 2014)
[Purpose] The purpose of this study was to investigate thoracic coupled motions of 20 Korean young individuals. [Methods] Thoracic motion of twenty healthy male college students aged 23.2±3.1 was examined. The coupled motions of the thoracic regions T1–4, T4–8, T8–12 were measured using a three dimensional motion capture system. [Results] Coupled axial rotation in the same direction as lateral bending was observed in T1–T4 and T4–T8 in the neutral, flexed, and extended postures of the thoracic spine. In T8–T12, coupled axial rotation in the same direction as lateral bending were observed in the neutral and flexed postures, while coupled axial rotation in the opposite direction was observed in an extended posture. [Conclusion] The patterns of coupled motions in the thoracic spine demonstrated some variability between postures and regions in vivo. However, coupled motions in the same direction were predominantly lateral flexion or axial rotation in the three postures.